ETIKA KEKUASAAN MENURUT AL QUR’AN (STUDI TERHADAP PRINSIP MUSYAWARAH DALAM TAFSIR JAMI’UL BAYAN FI TAFSIR AL QUR’AN) - Ilyas Husti (Jurnal An-Nur, 2015)
The Qur'an is the holy book that serves as a guide and mentor of man towards the good life and a safe . There is no problem whatsoever in people's lives are not getting the guidance and attention from the Koran . One that is considered important by the Qur'an is the ethics of power . Ethics power is ethical judge actions that must be obeyed by every leader if it wanted to implement the principles of true leadership . One of ethics Pneting in power is running principles of deliberation . Deliberation is a basic principle in which there is no absolute truth in power , and everyone can give sumbngsih thoughts for the future progress . With the principle of consultation , Islam has uproot kesemana - menaan and irregularities committed by the leaders